A Bibliometric Study of Organic Farming Research with a Focus on Global Collaboration, Main Themes, and Future Research Directions for the Period 2005–2024 - Loso Judijanto (Westscience Press, 2026)
This study presents a comprehensive bibliometric analysis of global research on organic farming published between 2005 and 2024. Using data retrieved from the Scopus database and analyzed through VOSviewer, the study maps publication trends, international collaboration networks, institutional linkages, and thematic structures within the field. The results indicate a significant increase in research output over the past two decades, reflecting the growing importance of organic farming within global sustainability discourse. Collaboration analysis reveals that research leadership remains concentrated in North America and Europe, particularly in the United States, Germany, the United Kingdom, and Italy, although developing countries are increasingly integrated into international research networks. Keyword co-occurrence and overlay visualizations show that organic farming research is strongly anchored in themes such as biodiversity, ecosystem services, climate change, carbon sequestration, and food security. Over time, the research focus has shifted from conservation and land-use concerns toward climate resilience, greenhouse gas mitigation, and smallholder livelihoods. Despite this progress, gaps remain in areas related to policy innovation, market governance, digital transformation, and economic scalability. Overall, the findings demonstrate that organic farming research has matured into an interdisciplinary and globally interconnected field that plays a strategic role in advancing sustainable agricultural systems.